INDONESIA CBM DEVELOPMENT CHALLENGES AND OPPORTUNITIES - Susilawati, Siti Sumilah Rita; Hadiyanto, Hadiyanto (Buletin Sumber Daya Geologi, 2006)
The increasing price of oil in the world market and the depleted national oil reserves while on the other hand there is a high dependency on oil as national main source of energy, promote the development of new energy alternative in Indonesia. Apart from oil, Indonesia is also known to have contained enormous resources of conventional gas, coal, hydropower andgeothermal. Furthermore due to its significant coal resources, coal bed methane becomes one of the new promising alternative energy in Indonesia.